Sikap keuangan, tingkat pendidikan, dan perilaku manajemen keuangan UMKM: Efek moderasi pengetahuan keuangan - Lasarus Wisma; Maria Rio Rita (Keberlanjutan, 2021)
The purpose of this study is to see how the influence of financial attitudes, education level on financial management behavior with financial knowledge as a moderating variable. The sample used in this study was 105 SMEs in the city of Salatiga, using the probability sampling technique. The instrument used in this research is a questionnaire, the tool used is partial least square (PLS). The results of this study indicate that financial attitudes and education level have a positive and significant effect on financial management behavior. Financial knowledge does not moderate the effect of financial attitude and education levels on financial management. So to improve the financial management behavior of MSME actors, it is necessary to improve financial and education levels. SMEs in Salatiga need to increase their financial experience through job training and work experience to enhance their financial attitude.